2006
DOI: 10.1677/jme.1.02174
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and its repair in lymphocytes and thyroid nodule cells during radioiodine therapy in patients with hyperthyroidism

Abstract: Radioiodine treatment of hyperthyroid patients with autonomous thyroid nodule leads to cellular DNA damage not only in thyrocytes but also in peripheral blood lymphocytes. The purpose of this study was to evaluate DNA breakage and base damage in thyrocytes and lymphocytes in patients treated with 131-I. In all the patients thyroid scintiscan was performed using 131-I. Damage to DNA was estimated by comet assay. Samples were taken before radioiodine treatment, and 12 and 54 days afterwards. Our results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Although comet assay is very well suited to the in vivo DNA damage investigation (Burlinson et al, 2007), a considerable differences were observed between different donor animals in course of this study (Table 2). Similar high diversity in DNA damage has been reported previously between human blood donors (Grzesiuk et al, 2006) and can be explained by differences in everyday individual behaviour of blood donors (for review, see Møller, 2000). The diet with transgenic triticale did not affect in this experiment the postnatal growth and development of mice and polymerase chain reaction used to analyses several tissues did not show the presence of transgenic DNA (PCR product of 637 bp) in any of the examined tissues: blood, kidney, liver, spleen and thigh muscle (Baranowski et al, 2006).…”
Section: Resultssupporting
confidence: 77%
“…Although comet assay is very well suited to the in vivo DNA damage investigation (Burlinson et al, 2007), a considerable differences were observed between different donor animals in course of this study (Table 2). Similar high diversity in DNA damage has been reported previously between human blood donors (Grzesiuk et al, 2006) and can be explained by differences in everyday individual behaviour of blood donors (for review, see Møller, 2000). The diet with transgenic triticale did not affect in this experiment the postnatal growth and development of mice and polymerase chain reaction used to analyses several tissues did not show the presence of transgenic DNA (PCR product of 637 bp) in any of the examined tissues: blood, kidney, liver, spleen and thigh muscle (Baranowski et al, 2006).…”
Section: Resultssupporting
confidence: 77%
“…Beside the genotoxic effects of toxic elements (especially metals), DNA damaging effects of radionuclides (although their concentrations in the transport water were extremely low) should not be neglected. The ability of radionuclides to induce primary DNA damage in terms of single and double strand breaks is well documented in earlier in vitro and in vivo studies (Pedraza Lopez et al, 2000;Calini et al, 2002;Kopjar and Garaj-Vrhovac, 2005;Grzesiuk et al, 2006;Morita et al, 1992). Therefore, when discussing the overall levels of damage as recorded by the alkaline comet assay, possible synergistic effects of heavy metals and radionuclides should also be anticipated.…”
Section: Discussionmentioning
confidence: 92%
“…In thyroid cells, I-131 induces DSBs detectable as γH2AX or 53BP1 foci (Hershman et al . 2011), as well as clustered DNA damage detected by Comet assay (Grzesiuk et al . 2006).…”
Section: Discussionmentioning
confidence: 99%